2021
DOI: 10.1038/s41586-021-03830-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-mesenchymal units control ILC2 and obesity via a brain–adipose circuit

Abstract: Signals from sympathetic neurons and immune cells regulate adipocytes contributing to fat tissue biology. Interactions between the nervous and immune systems have recently emerged as major regulators of host defence and inflammation 1-4 . Nevertheless, whether neuronal and immune cells cooperate in brain-body axes to orchestrate metabolism and obesity remains elusive. Here we report a novel neuro-mesenchyme unit that controls group 2 innate lymphoid cells (ILC2), adipose tissue physiology, metabolism and obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 60 publications
2
65
0
Order By: Relevance
“…Hence, we postulate that increased AMP expression in Upd2-AIM-may impinge on systemic processes, perhaps by altering brain function, and this might underlie their increased hunger feeding motivation (Figure 5D). Furthermore, the increased lipolysis we observe with Upd2-AIM over-expression flies (Figure 5C) aligns with the emerging role in mammalian studies for AMPs in TAG mobilization [86, 87]. In sum, our current working hypothesis is that the secreted immune peptide signature downstream of Upd2 nuclear retention enables the organism to adapt to starvation and promotes hunger-driven feeding.…”
Section: Discussionsupporting
confidence: 80%
“…Hence, we postulate that increased AMP expression in Upd2-AIM-may impinge on systemic processes, perhaps by altering brain function, and this might underlie their increased hunger feeding motivation (Figure 5D). Furthermore, the increased lipolysis we observe with Upd2-AIM over-expression flies (Figure 5C) aligns with the emerging role in mammalian studies for AMPs in TAG mobilization [86, 87]. In sum, our current working hypothesis is that the secreted immune peptide signature downstream of Upd2 nuclear retention enables the organism to adapt to starvation and promotes hunger-driven feeding.…”
Section: Discussionsupporting
confidence: 80%
“…In turn, these cells produce glial-derived neurotropic factor, the receptor for which, RET, is particularly highly expressed on visceral adipose tissue ILC2s. This interaction leads to the production of type 2 cytokines and enkephalins by ILC2s, which promotes beiging of WAT and counteracts the development of obesity following a high-fat diet 78 . In addition, it was recently shown that ILC2s regulate the downstream effects of obesity, namely metabolic syndrome , limiting both the onset of insulin resistance and established insulin resistance in a mouse model of obesity 79 .…”
Section: Ilc2s In Adipose Tissue Homeostasismentioning
confidence: 99%
“…The immune cells highly express β2 adrenergic receptor ( Adrβ2 ), which confers their responsiveness to NE. However, no significant effect on adipose metabolism was observed upon deletion of Adrβ2 in macrophage or ILC2s ( 64 , 65 ). It is yet to be known how adrenergic signaling may affect the cellular pathways in the adipose immune cells and thereby influence energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%